Asymptotic behavior of the wave equation solution with nonlinear boundary damping and source term of variable exponent-type - Adel M. Al-Mahdi; Mohammad M. Al-Gharabli; Mohammad Kafini (AIMS Mathematics, 2024)
In this study, a nonlinear damped wave equation within a bounded domain was considered. We began by demonstrating the global existence of solutions through the application of the well-depth method. Following this, a general decay rate for the solutions was established using the multiplier method alongside key properties of convex functions. Notably, these results were derived without the imposition of restrictive growth assumptions on the frictional damping, making this work an improvement and extension of previous findings in the field.